Prealbumin to fibrinogen ratio is closely associated with diabetic peripheral neuropathy. Issue 8 (August 2020) - Zang, Shufei; Shi, Lei; Zhao, Jinying; Yang, Min; Liu, Jun; Ding, Heyuan
Abstract : The aim of our study was to explore the diagnostic value of prealbumin to fibrinogen ratio (PFR) for predicting prognosis with the optimal cut-off value in diabetic peripheral neuropathy (DPN) patients. A total of 568 type 2 diabetes mellitus (T2DM) patients were enrolled in this study. The values including Toronto clinical neuropathy score (TCNS), nerve conduction velocity (NCV), vibration perception threshold (VPT), blood cells count, biochemical parameters, fibrinogen and PFR were recorded. The patients were divided into tertiles based on admission PFR value. First, clinical parameters were compared among the groups. Secondly, a logistic regression and ROC analysis were performed as the statistical model. The percentage of DPN, TCNS and VPT were significantly higher in the lowest PFR tertile than in the middle PFR tertile and the highest PFR tertile ( P < 0.01–0.001). NCV was significantly lower in lowest PFR tertile than in the middle PFR tertile and the highest PFR tertile ( P < 0.01–0.001). The Spearman correlation analysis showed that PFR was negatively correlated with TCNS and VPT ( P < 0.001), while PFR was positively correlated with median motor NCV ( P < 0.001), peroneal motor NCV ( P < 0.001), median sensory NCV ( P < 0.001), and peroneal sensory NCV ( P < 0.001). After adjusting these potentially related factors, PFR was independently related to DPN ( P  = 0.007). The area under ROC curve was 0.627. This study finds the first evidence to suggest PFR may be the key component associated with DPN in T2DM, while PFR might underlie the pathophysiologic features of DPN.